PENGARUH KUALITAS LAYANAN KEPERCAYAAN DAN LOKASI TERHADAP LOYALITAS ANGGOTA (Studi Pada Kantor BMT Walisongo Gajahmungkur Semarang) - Rizal Fatkhul Rafa, 14.05.51.0175; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2018)
The purpose of this study is to determine the effect of Quality Service, Trust, And Location Against Member Loyalty On Office BMT Walisongo Gajah Mungkur Semarang. This study also aims to determine the influence of the three independent variables on the dependent variable and to know which variable is the most dominant influence among the three independent variables to the dependent variable, this type of research uses qualitative research, with a membership population of 100 members. Data collection using questionnaires with Likert scale. Based on the results of research shows that there is a significant influence of service quality variables on the loyalty of BMT members Walisongo Gajah Mungkur Semarang.Terdapat significant influence belief variable on the loyalty of BMT members Walisongo Gajah Mungkur Semarang.Terdapat significant influence Location variables influence the loyalty BMT members Walisongo Semarang. Keywords: Service quality, trust, location, and member loyalty